The Levels of Authentic Happiness Among Women Who Married at A Young Age at Kaliwungu Village, Ngunut Sub-District, Tulungagung District - Sal Shabila Ayumas Puteri (Jurnal Ilmiah Kesehatan, 2023)
Early to late adolescents (aged 12-21) experience diverse and fluctuating psychological, mental, mind, and physical dynamics. Living in a household is also not easy and faces many problems. Thus, getting married at a young age potentially influences authentic happiness among women. This paper describes the levels of authentic happiness among women who married at a young age. This research used a quantitative method and literature studies. The population was women who married at a young age in Kaliwungu Village, Ngunut Sub-District, Tulungagung District. There were ten respondents. Data collection was by distributing authentic happiness questionnaires to respondents. The questionnaire consists of 25 statements from the instrument Authentic Happiness Inventory owned by Martin Seligman. Results showed that the score of authentic happiness in all respondents ranges from 75 to 125. In addition, two respondents have moderate levels of authentic happiness, and eight have high. In conclusion, most women who married at a young age had high levels of authentic happiness, and little had moderate.